Ophthalmic Manifestations and Genetics of the Polyglutamine Autosomal Dominant Spinocerebellar Ataxias: A Review - Park, Jun Young; Joo, Kwangsic; Woo, Se Joon (Frontiers in Neuroscience, 2020)
Spinocerebellar ataxias (SCAs) are a genetically diverse group of mainly autosomal dominant disorders in which cerebellar disease can occur in isolation or concomitantly with brainstem or retinal abnormalities. Although autosomal dominant cerebellar ataxias have different clinical features and different disease-causing genes, they share a common underlying mutational mechanism—an expanded trinucleotide repeats encoding a tract of glutamine amino acids. Eye movement abnormalities are prominent in both cerebellar and brainstem diseases; hence, the recognition and differentiation of SCAs are important to an ophthalmologist for proper diagnosis and evaluation. In addition, certain types of SCAs such as SCA type 7 are characterized by a combination of cerebellar ataxia and visual loss mainly due to retinal degeneration. The severity of the retinopathy can vary from occult macular photoreceptor disruption to foveal retinal atrophy and is correlated with the number of cytosine–adenine–guanine (CAG) repeats. The value of using optical coherence tomography in conjunction with electrodiagnostic and genetic testing is emphasized as the combination of these tests provide critical information regarding the etiology, morphological evaluation, and functional significances. Studies have suggested that the mutated form of ataxin tends to aggregate into nuclear inclusions and causes cellular loss of photoreceptors through a toxic effect that induces a downregulation of genes involved in the phototransduction, development, and differentiation of photoreceptors such as CRX, a nuclear transcription factor predominantly expressed in retinal photoreceptor cells. However, it is unclear how the CAG-expanded form of ataxin causes degenerations restricted to only certain populations of neurons. SCA types 1, 2, 3, 6, and 7 are the most common, comprising approximately 80% of autosomal dominant SCA cases. In this review, we have described and discussed the most common SCAs with particular attention to their ophthalmic features, neurodegenerative mechanisms, genetics, and future perspectives.